PAINT: Priority aware interference mitigation techniques for improving coexistence in home area networks of smart grid. (12th July 2020) - Nahar, Badrun; Roy, Jaya; Karmaker, Amit; Craig, Andrew; Alam, Mohammad Shah
Summary: As smart grid (SG) home area networks (HANs) communicate with various smart devices such as meters, sensors, and actuators on a 2.4‐GHz unlicensed band, the coexistence of different wireless technologies in such networks is a common phenomenon due to the overlapping of channels. In this research, homogeneous and heterogeneous interference are considered to address the coexistence problem in smart utility networks (SUNs). The homogeneous interference is mitigated by utilizing the contention free period (CFP) and the contention access period (CAP) of the MAC layer superframe of IEEE 802.15.4g designed for SUNs. This frame is used to get access for the channel. For this, a slotted CSMA/CA algorithm is used for various priority levels of data with adjustable backoff period (BP) and clear channel assessment (CCA) period in order that nodes (devices) with high priority can achieve high probability of channel access. By modeling the proposed scheme using the Markov chain, the exactness of the proposed scheme is assessed based on throughput, channel access delay, energy consumption per bit, and probability of successful data transmission and collision. A performance evaluation of the proposed scheme is further investigated by comparing it with the existing scheme PA‐MAC. In addition, a channel switching mechanism is explored to mitigate the heterogeneous interference with the help of a Naive Bayes classifier prediction. Finally, the prediction indicates that by choosing the non‐coexisting and the non‐overlapping channel, the proposed channel switching mechanism effectively mitigates the heterogeneous interference. Abstract : Novel techniques to improve the coexistence of different wireless technologies in home area networks (HANs) of smart grid by minimizing the interference and heterogeneous interference that exist in HANs are considered here. Utilizing the contention free period (CFP) and the contention access period (CAP) in MAC layer superframe of IEEE 802.15.4g, the homogeneous interference is significantly reduced. Finally, an efficient channel switching scheme based on Naive Bayes classifier is implemented to mitigate the heterogeneous interference.